Assessment of Intelligence of Duchenne Muscular Dystrophy (DMD) Children and Adolescents and Parental Stress in a Muscular Dystrophy Center in Nepal - Rana, Mita; Adhikari, Sirjana; Pradhan, Monalisa (Journal of Nepal Paediatric Society, 2017)
Correction: On 21st May 2017 the word 'Adults' was changed to 'Adolescents' in the title of the article on NepJOL. The PDF was correct and has not been changed. Introduction: Duchene Muscular Dystrophy (DMD) is an X-linked developmental disorder characterized by progressive muscle weakness, demanding many psychosocial adjustments for both parents and children; learning and behavioral problems, changing values, expectations, roles and responsibilities, separation and loss that lead to parental stress. This study is an attempt to explore the level of Intelligence Quotient of children and adolescents with DMD and further elucidate aspects of parental stress. Material and Methods: The study involved 30 children and adolescents with DMD, chosen by convenient sampling method and one parent each, during their regular medical evaluation at the Duchene Muscular Dystrophy Foundation in Nepal. Measures used to collect data were the Draw a Man Test and Cohen’s Perceived Stress Scale. Results: Age of the DMD children and adolescents ranged between 4 to 19 years with mean age 12.01 ± 6.26 years, 93.94% were male. 53.33% of the parents reported having average level of stress and 63.33% of DMD children and adolescents had average level of Intelligence Quotient (IQ > 70), 16.67% had mild (IQ between 50-69) and 10% each were found to have moderate and severe intellectual disability. Significant negative correlation (r = -0.393, p=0.05) was found between the level of intellectual functioning of DMD children and level of parent’s perceived stress. Conclusion: Most of the parents experienced average to severe level of stress based on the duration of illness and the level of intellectual functioning of their DMD child. Parents experienced greater level of stress with children having low intelligence. J Nepal Paediatr Soc 2016;36(3):227-231